How intravitreal anti-vascular endothelial growth factor initial dosing impacts patient outcomes in diabetic macular oedema - Rishi P. Singh; David Tabano; Blanche L. Kuo; Andrew LaPrise; Theodore Leng; Eunice Kim; Meghan Hatfield; Vincent Garmo (BMC Ophthalmology)
Abstract Background Intravitreal anti-vascular endothelial growth factor (VEGF) treatment for diabetic macular oedema (DME) may begin with several initial monthly doses. Characteristics, treatment patterns and outcomes were compared for eyes with DME that did and did not receive such initial doses. Methods This was a retrospective database study using American Academy of Ophthalmology Intelligent Research in Sight® Registry data (01/01/15–31/12/20; index period). Eligible adults had documented DME within 2 months of first anti-VEGF treatment (index date), data available for 12 months beforehand, and ≥ 1 visual acuity (VA) recording ≤ 60 days before index date. Eyes must have received intravitreal anti-VEGF injections during the index period, but none in the prior 12 months. Characteristics and outcomes for eyes with initial doses (three injections within 100 days of index date) were compared with those without. Multivariate Cox Proportional Hazards modelling estimated predictors for treatment discontinuation, re-initiation, or switch; Generalized Estimating Equations-adjusted modelling estimated characteristics associated with receiving initial doses. Demographics and characteristics were summarised. Injection frequency and number, and VA were determined annually for ≤ 6 years. Discontinuations, reinitiations and switches were compared. Results Included were 217,696 eyes (n = 77,769 initial; n = 139,927 non-initial) from 166,868 patients. Mean (SD) baseline VA was numerically higher for eyes with versus without initial doses (63.0 [18.1] vs. 62.5 [19.8] letters); this remained during follow-up. Based on modelling results, Eyes with initial doses received more injections (mean [standard deviation (SD)] 11.6 [8.9] vs. 6.1 [6.8] injections) more frequently (interval 7.6 [2.8] vs. 12.6 [7.7] weeks) than eyes without. These differences occurred across follow-up years. Discontinuation (45.7% vs. 63.8%), re-initiation (17.2% vs. 25.0%), and switch (24.5% vs. 31.5%) were less common with initial doses. Asian, Black, and patients of other/unknown race were less likely (P < 0.01) to receive initial doses than White patients, as were Medicare/Medicaid-insured patients versus commercially insured patients (P < 0.01). Conclusions Various sociodemographic factors associate with initial anti-VEGF doses, including race, ethnicity and insurance. Although eyes with frequent initial doses maintained higher VA than those without, they also receive more injections over time. Further research may elucidate the impact of frequent initial doses versus total injection number on DME outcomes.